2007 40th Annual Hawaii International Conference on System Sciences (HICSS'07) 2007
DOI: 10.1109/hicss.2007.589
|View full text |Cite
|
Sign up to set email alerts
|

User Security Behavior on Wireless Networks: An Empirical Study

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…There are also some other up-to-date studies pointing the user security behaviors on wireless public networks. Chenoweth et al [4,5] examined the results of their empirical study, which mainly marks the insecurity of wireless networks due to their natural vulnerabilities rather than the password use.…”
Section: Password Related Experiments In Literaturementioning
confidence: 99%
“…There are also some other up-to-date studies pointing the user security behaviors on wireless public networks. Chenoweth et al [4,5] examined the results of their empirical study, which mainly marks the insecurity of wireless networks due to their natural vulnerabilities rather than the password use.…”
Section: Password Related Experiments In Literaturementioning
confidence: 99%
“…The authors suggested WPA-PSK instead of WEP and consider Media Access Control (MAC) address filtering as a security mechanism. Chenoweth et al (2007) Conducted study of users' behavior in a university. The study finds that 9% of 3,331 of personal computers on campus do not have firewalls properly configured on them.…”
Section: Related Workmentioning
confidence: 99%
“…A more user focused empirical study by [8] which was carried out on users' behavior in a university shows that 9% of 3,331 of personal computers on campus do not have firewalls properly configured on them. In addition to this, 60% of wireless networks did not use any good form of authentication or encryption according to a survey by panda international and also vulnerability checks indicated a good number of users not having firewalls on their computers.…”
Section: Wireless Network Users and Policiesmentioning
confidence: 99%